Volatile profile characterisation of Chilean sparkling wines produced by traditional and Charmat methods via sequential stir bar sorptive extraction. (15th September 2016) - Ubeda, C.; Callejón, R.M.; Troncoso, A.M.; Peña-Neira, A.; Morales, M.L.
Highlights: In general profile of Chilean sparkling wines stand out esters, alcohols and acids. Headspace and immersion sequential extraction using two PDMS twisters was the best. Traditional wines had higher presence of ethyl esters than Charmat wines. Charmat wines presented higher amounts of acetic esters than traditional wines. Abstract: The volatile compositions of Charmat and traditional Chilean sparkling wines were studied for the first time. For this purpose, EG-Silicone and PDMS polymeric phases were compared and, afterwards, the most adequate was selected. The best extraction method turned out to be a sequential extraction in the headspace and by immersion using two PDMS twisters. A total of 130 compounds were determined. In traditional Chilean sparkling wines, ethyl esters were significantly higher, while acetic esters and ketones were predominant in the Charmat wines. PCA and LDA confirmed the differences in the volatile profiles between the production methods (traditional vs. Charmat).